Expediting Trade : Impact Evaluation of an In-House Clearance Program - Fernandes, Ana M.; Hillberry, Russell; Berg, Claudia (World Bank, Washington, DC, 2016)
Despite the importance of trade facilitation as an area of trade and development policy, there have been very few impact evaluations of specific trade facilitation reforms. This paper offers an evaluation of in-house clearance, a reform that allows qualified firms in Serbia to clear customs from within their own warehouse rather than at the customs office. The pooled synthetic control method applied here offers a novel solution to many of the empirical challenges that frustrate efforts to evaluate trade facilitation reforms. The method is used to estimate causal impacts on trade outcomes for 21 firms that adopted in-house clearance for import shipments. The program compressed the distribution of clearance times for adopting firms, but the estimated effects on median clearance times, inspection rates, and import value were not statistically significant. Tests for heterogeneous program impact do not indicate that the program affected adopting firms differently. Overall, the results suggest that the most evident benefit of the program for participating firms is reduced uncertainty about clearance times.